Attributes of conception of relational continuity: an essential component of the integration of services for frail older people - Gagnon, Dominique (Igitur, Utrecht Publishing & Archiving, 2009)
PURPOSE: Present the results of an exploratory study which aimed to identify the attributes of relational continuity as conceived by the actors involved in the organization of services to frail older people. THEORY: The lengthening of the duration of life with autonomy loss warrants a transformation of the response to the needs of older people. The organization of services must evolve from a hospital-centered model to a residence-centered model better adapted to long-term care. This refocus on residential care provokes a multiplication of service providers which must be coordinated to ensure continuity of care [1]. Amongst the three forms of continuity (informational, management and relational) [2], relational continuity appears as the least documented and most difficult to measure. METHODS: Twenty-seven interviews with practitioners, managers, family caregivers and users were conducted and analysed using a content analysis approach. RESULTS AND CONCLUSIONS: While the family caregivers and users stressed the psycho-affective nature of the care relationship, the practitioners viewed it as a means to ensure the adequacy of services. From the user's viewpoint, the relationship is not the responsibility of one professional, but of a collective effort that may carry his voice across the services organization.